Fintech and Sustainable Development: A Systematic Review of Financial Inclusion, Green Finance, and Digital Transformation - Isma Addi; Muhammad Inam Makki Khan; Iryna Shkodina (Start-up and Financial Technology, 2026)
Objective: This study aims to systematically examine the role of Financial Technology (FinTech) in advancing sustainable development by identifying key research themes, trends, and gaps that link digital financial innovation with the Sustainable Development Goals (SDGs). Research Design & Methods: A qualitative Systematic Literature Review (SLR) was employed using data from Scopus, Web of Science, and Google Scholar data (2017–2025). After a rigorous screening process, total of 259 articles were analyzed bibliometrically, with 48 full-text articles examined qualitatively using VOSviewer and thematic analysis to identify research clusters, trends, and knowledge gaps.Findings: The research findings reveal four major research clusters: (1) green finance and environmental sustainability, (2) economic growth and innovation, (3) core technologies such as artificial intelligence (AI) and blockchain, and (4) financial inclusion and digital adoption. The results indicate a transformational pathway in which technological innovation enhances financial inclusion and economic development, ultimately supporting sustainability outcomes. However, significant gaps remain, particularly in integrating multiple technologies and in directly linking FinTech to green finance and the implementation of the SDGs.Implications: This study highlights the need for an integrated regulatory framework, improved digital infrastructure, and enhanced financial literacy to maximize FinTech’s contribution to sustainable development, especially in developing countries. Contribution & Value Added: This study contributes by providing a comprehensive framework that connects FinTech, sustainability, and the SDGs, while identifying critical research gaps and future directions toward a holistic, policy-driven, sustainable financial ecosystem.